i got the following: (8y)(dy/dx) + 10x^4 = 0 now it solves to: dy/dx = -(5x^4)/(4y) just dont understand how its come to that?
Last edited by CaptainBlack; Sep 8th 2007 at 03:11 AM. Reason: change frown back to :(
Follow Math Help Forum on Facebook and Google+
Originally Posted by taurus i got the following8y)(dy/dx) + 10x^4 = 0 now it solves to: dy/dx = -(5x^4)/(4y) just dont understand how its come to that? $\displaystyle 8y \frac{dy}{dx} + 10x^4 = 0$ $\displaystyle 8y \frac{dy}{dx} = -10x^4$ $\displaystyle \frac{dy}{dx} = -\frac{10x^4}{8y}$ $\displaystyle \frac{dy}{dx} = -\frac{5x^4}{4y}$ -Dan
yea but y 5/4? How?
Originally Posted by taurus yea but y 5/4? How? Ummm... What? $\displaystyle \frac{10}{8} = \frac{2 \cdot 5}{2 \cdot 4} = \frac{5}{4}$ -Dan
View Tag Cloud